Nekateri vidiki kakovosti ambulantne obravnave bolnikov s sladkorno boleznijo v Splošni bolnišnici Celje - Veninšek, Gregor (Zdravniški vestnik, 2001)
Background. The prevalence of diabetes is growing. Development of chronic complications of diabetes can be prevented by intensive treatment. It is of utmost importance to know characteristics of treated population to follow it up and adjust measures. We conducted an evaluation of population of diabetic patients treated in Celje General Hospital. Methods. We studied 156 outpatients treated in Celje General Hospital in January 2000. We collected data on basic anthropologic characteristics, data on type, duration and treatment modality of diabetes, metabolic parameters, risk factors for development and presence of chronic complications. We specially a subgroup ofdiabetics treated in our outpatient service less than two years. Results. The mean age of patients was 58 years. They have been treated for diabetes in average for 10 years. 94% of patients were type 2.3% of patients had secundarydiabetes and 3% had type 1 diabetes. 74% were overweight. 37% of patients had HbA1c equal or below 7.5%. 45% of patients had LDL equal or below3.0 mmol/l, and 52% of patients had blood pressure equal or below 140/90 mmHg. Retinopathy was present in 34%, renal failure in 10% and neuropathy in 35%. Amputation on a lower limb had had 1% of patients. 56% of patients were treated only with oral hypoglycaemic drugs, 6% diet only and 38% of patients were treated with insulin either alone or in combination with oral hypoglycaemic drugs. In diabetics that we treat less than two years at least one late complication was present in 73%. Conclusions. Diabetics are referred to our service when complications of treatment of diabetes or chronic complications of diabetes are present. In the beginning of year 2000 we achieved acceptable value of HbA1c in 37% of patients, that of LDL and blood pressure in 45% and 52%, respectively. Prevalence of chronic complications of diabetes was comparable with the data from the literature.
Keywords: Ambulantna oskrba; Ambulatory care; bolniki; Dejavniki tveganja; Diabetes melitus; Diabetes mellitus; Diabetic angiopathies; Diabetic neuropathies; Diabetična nevropatija; Diabetične angiopatije; Diagnosis; Risk factors; sladkorna bolezen; splošna medicina; Therapy; zdravljenje